2017
DOI: 10.3892/ol.2017.5748
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Thevetia peruviana flowers enhances TNF-α and TRAIL-induced apoptosis of human cervical cancer cells via intrinsic and extrinsic pathways

Abstract: Abstract. Tumor necrosis factor-α (TNF-α) and TNF-related apoptosis-inducing ligand (TRAIL) are promising candidates for cancer treatment due to their ability to induce apoptosis through death receptor stimulation. However, their usage may be limited due to the resistance of cancer cells to TNF-α-and TRAIL-induced apoptosis. Currently, there is interest in screening for natural products that can sensitize cancer cells to TNF-α-and TRAIL-induced apoptosis for their use in combination with TNF-α or TRAIL. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[79][80][81][82][83][84][85][86] The expression and activity of TNF-α (encoded by TNF) is associated with the apoptosis, chemosensitivity, DNA damage response, necrosis, proliferation, invasion, and EMT of CC cells, and its polymorphisms are further correlated with the risk of development, progression, and malignancy in patients with CC. [87][88][89][90][91][92][93][94][95][96][97][98][99][100] The genetic or epigenetic malfunction of p53 (encoded by TP53), a key tumor suppressor that coordinates the cell cycle process, proliferation, apoptosis, DNA damage repair, and metabolism, can drive CC pathogenesis; therefore, the restoration of its expression or functional activity has been suggested as a potential strategy for treating CC. [101][102][103] In addition, elevated expression and polymorphisms of TP53 are commonly observed in CC tissues compared to normal cervical tissues, and correlated with the poor clinical outcome of patients with CC.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81][82][83][84][85][86] The expression and activity of TNF-α (encoded by TNF) is associated with the apoptosis, chemosensitivity, DNA damage response, necrosis, proliferation, invasion, and EMT of CC cells, and its polymorphisms are further correlated with the risk of development, progression, and malignancy in patients with CC. [87][88][89][90][91][92][93][94][95][96][97][98][99][100] The genetic or epigenetic malfunction of p53 (encoded by TP53), a key tumor suppressor that coordinates the cell cycle process, proliferation, apoptosis, DNA damage repair, and metabolism, can drive CC pathogenesis; therefore, the restoration of its expression or functional activity has been suggested as a potential strategy for treating CC. [101][102][103] In addition, elevated expression and polymorphisms of TP53 are commonly observed in CC tissues compared to normal cervical tissues, and correlated with the poor clinical outcome of patients with CC.…”
Section: Discussionmentioning
confidence: 99%
“…possess potential anticancer activities. Managit C et al [13] reported that the ethanolic extract of flowers were effective against the HeLa cells. Silva AR et al [14] Testified that the methanolic extract of the fruits possess anticancer potential against the human breast, colorectal, prostate and lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ethanolic FE of Thevetia peruviana stimulated apoptosis of cervical cancer HeLa cells triggered by TNFα or TRAIL, two ligands of death receptors, by activating caspase-3 and PARP. Notably, FE of T. peruviana diminished the expression of the anti-apoptotic protein survivin (Managit, Sakurai, and Saiki, 2017) A FE containing essential oils of Pallines spinosa decreased cell viability of breast cancer cells while a minor effect was detected in immortalized mammary epithelial cells (Saleh et al, 2017). This effect was accompanied by a decrease of the anti-apoptotic protein Bcl-2 and an increase of the pro-apoptotic protein Bax Flowers from Antirrhium majus are among the most popular edible flowers, frequently used from preparing foods and drinks.…”
Section: Extracts From Flowers With Anticancer Effectmentioning
confidence: 97%